Engaging employees in value cocreation: interplay among firm, employee, and supervisor è®©åå·¥åä¸ä»·å¼å ±åï¼å ¬å¸ãåå·¥åä¸»ç®¡ä¹é´çç¸äºä½ç¨ - Amin, M. (Routledge, 2022)
Research on value cocreation with customers is considerable, yet questions remain regarding whether and how to engage frontline employees (FLEs) in such efforts. Adopting the abilityâmotivationâopportunity perspective, we conceptualize service firmsâ interaction capabilities as ability, employeesâ motivation to cocreate value with customers (EMCCV) as motivation, and supervisor proactive personality as opportunity. This empirical investigation thereby addresses the effect of service firmsâ interaction capabilities on EMCCV and employeesâ subsequent value cocreation behaviors (participation and citizenship). Data collected from 311 FLEs in automotive industries reveal that EMCCV mediates the positive effects of firmsâ interaction capabilities (developmental, relational, ethical, and individuated) on employeesâ value cocreation behaviors. Further, supervisor proactive personality significantly strengthens the effects of firmsâ interaction capabilities on EMCCV. Supplementary analyses uncover a stronger indirect positive association between firmsâ interaction capabilities and employeesâ value cocreation behaviors (via EMCCV) when employees perceive their supervisors as proactive. These findings highlight the crucial roles of firmsâ interaction capabilities and supervisorsâ personalities in motivating FLEsâ value cocreation behaviors during service exchanges. They also reveal practical options for promoting more inclusive, sustainable economic growth and guidelines for fostering and promoting improved working conditions for FLEs (UN Sustainable Development Goal 8). Â© 2022 Informa UK Limited, trading as Taylor & Francis Group.